Rozwiaz uklad rownan
1)
x+y=30
1,2x-0,05y=21

2)
x-27=0,1x
0,9x=27

rozwiaz nierownaosc
1)
x+2-0,4 (4x-1)>0

2)
(2x+3) do kwadratu +(3x-1)(3x+1)-(x-2) do kwadratu > (4x-5) do kwadratu - - (2x+3)(2x-3)+26x

3)
x/2 + 2 + 2/3 (x/2 + 2 ) = x-1

4)
3*0,1=(3+x)*0,06

3

Odpowiedzi

2010-04-02T14:07:54+02:00
Rozwiaz uklad rownan
1)
{x+y=30 /×(-1,2)
{1,2x-0,05y=21
{-1,2x-1,2y=-36
{1,2x-0,05y=21
-1,25y=-15/:(-1,2)
y=12,5

x+y=30
x=30-y
x=30-12,5
x=17,5

2)
{x-27=0,1x
{0,9x=27 /:(0,9)
{x-0,1x=27
{x=30
{0.9x=27 /:(0,9)
x=30

2010-04-02T14:30:29+02:00
1)
x+y=30 /*(-1,2)
1,2x-0,05y=21
-1,2x-1,2y=-36
1,2x-0,05y=21
-1,25y=-15/:(-1,25)
y=12
x=30-y
x=30-12
x=18
Odp. X=18, y=12

2)
x-27=0,1x
0,9x=27
x-0,1x=27
0,9x=27/:0,9
x=30
Odp. x=30

1)
x+2-0,4 (4x-1)>0
x-2-0,16+0,4>0
x>2+0,16-0,4
x>1,76


2)
(2x+3) do kwadratu +(3x-1)(3x+1)-(x-2) do kwadratu > (4x-5) do kwadratu - - (2x+3)(2x-3)+26x
(2x+3)²+(3x-1)(3x+1)-(x-2)²> (4x-5)²-(2x+3)(2x-3)+26x
4x²+12x+9+9x²-1-x²-4x+4>16x²-40x+25-4x²-9+26x
4x²+12x+9x²-x²-4x-16x²+40x+4x²-26x>-9+25-4+1-9
48x>4/:48
x>0,8
3)
x/2 + 2 + 2/3 (x/2 + 2 ) = x-1/*6
3x+12+4(x/2+2)=6x-6
3x+12+2x+8=6x-6
3x+2x-6x=-6-12-8
-x=-26/*(-1)
x=26
4)
3*0,1=(3+x)*0,06
0,3=0,18+0,06x
0,3-0,18=0,06x
0,12=0,06x/:0,06
x=2






2010-04-02T14:57:30+02:00
1)
x+y=30
1,2x-0,05y=21|×20

x+y=30
24x-y=420

25x=450|÷25
x=18

x+y=30
18+y=30
y=12

x=18
y=12
2)
x-27=0,1x
0,9x=27

x-0,1x=27
0,9x=27

0,9x=27
0,9x=27

x=30

1)
x+2-0,4(4x-1)>0
x+2-1,6x+0,4>0
-0,6x>-2-0,4
-0,6x>-2,4|÷(-0,6)
x<4
x∈(-nieskończoność, 4)
2)
(2x+3)²+(3x-1)(3x+1)-(x-2)²>(4x-5)²-(2x+3)(2x-3)+26x
4x²+12x+9+9x²-1-(x²-4x+4)>16x²-40x+25-(4x²-9)+26x
4x²+12x+9+9x²-1-x²+4x-4>16x²-40x+25-4x²+9+26x
30x>26|÷30
x>26/30
x>13/15
x∈(13/15; nieskończoność)
3)
x/2+2+⅔(x/2+2)=x-1
x/2+2+2x/6+4/3=x-1
x/2+2x/6 - x=-1-2-4/3
x/2+2x/6 - x=-3-1⅓
x/2+2x/6 - x=-4⅓|×6
3x+2x-6x=-26
-x=-26
x=26
4)
3×0,1=(3+x)×0,06
0,3=0,18+0,06x
0,06x=0,3-0,18
0,06x=0,12|÷0,06
x=2